Screening tumor specificity targeted by arnicolide D, the active compound of Centipeda minima and molecular mechanism underlying by integrative pharmacology. (10th January 2022) - Yao, Jingjing; Shen, Qinghong; Huang, Min; Ding, Ming; Guo, Yajuan; Chen, Wenbo; Lin, Yuefang; Zheng, Yaqiu; Yu, Shaofang; Yan, Wenxin; Su, Tao; Liu, Zhongqiu; et al.
Abstract: Ethnopharmacological relevance: Herb-derived anti-tumor agents, such as paclitaxel and vincristine, exert significant but varied effectivenesses towards different cancer types. Similarly, Centipeda minima (CM) is a well-known traditional Chinese medicine that has been used to treat rhinitis, relieve pain and reduce swelling, and recently found to exert overwhelming anti-tumor effects against breast cancer, colon cancer, and nasopharyngeal carcinoma with different response rates. However, what is the optimizing cancer model that benefits most from CM, and what is the specific target underlying still require more exclusive and profound investigations. Aims of the study: This study aimed to explore the dominant tumor model and specific target of CM by integrative pharmacology and biological experiments. Materials and methods: The most predominant and specific cancer types that are sensitive to CM were screened and identified based on a combination network pharmacology and bioinformatics analysis. Compound-target network and protein-protein interaction of CM-related cancer targets were carried out to determine the most abundant active compound. Simultaneously, the priority target responsible for CM-related anti-tumor efficacy was further validated by molecular docking and in vitro experiments. Results: In total, approximately 42% (8/19) of the targets were enriched in prostate cancer ( p = 1.25E-09), suggesting prostate cancer would be the most sensitive tumor response to CM-related efficacy. Furthermore, we found that arnicolide D (ARD), the most abundant and representative active compound of CM, could directly bind to Src with binding energy of -7.3 kcal/mol, implying Src would be the priority target responsible for CM-related anti-tumor efficacy. Meanwhile, the results were further validated by solvent-induced protein precipitation (SIP) assay. In addition, PCR and WB results also revealed that either CM or ARD could not influence the gene expression of Src, while significantly decreased its protein expression instead, which further suggested that ARD might markedly shortene the Src protein half-life to promote Src protein degradation, thereby achieving significant anti-prostate cancer efficacy. Conclusion: Our findings not only suggest CM as a promising Src-targeting candidate for prostate cancer treatment, but also bring up a strategy for understanding the personalization of herbal medicines by using integrative pharmacology. Graphical abstract: Image 1 Highlights: Prostate cancer would be the most sensitive tumor response to CM-related efficacy by integrative pharmacology. ARD could directly bind to Src, implying Src would be the priority target responsible for CM-related anti-tumor efficacy. ARD, the active compound of CM, may be a promising Src-targeting candidate for prostate cancer treatment.